Using a bioindicator species to evaluate soil limitations for the recruitment of a recalcitrant tree seed species of Central Chile threatened by climate change - Morales, Narkis S.; Fernández, Ignacio C.; Riquelme-Alarcón, Joaquín; Arellano, Eduardo C. (Frontiers in Forests and Global Change, 2025)
Human activities have significantly altered over three-quarters of the Earth’s land surface, intensifying in the last century and threatening remaining ecosystems with ongoing land use changes and climate change. In Chile’s Mediterranean zone, habitat degradation and climate change pose severe threats to biodiversity, particularly affecting endemic tree species with recalcitrant seeds, such as Beilschmiedia miersii, which can face recruitment limitations due to changing environmental conditions and prolonged droughts. This study aims to determine if soil and site-specific conditions at B. miersii population sites limit seed germination and establishment. The study used Lens culinaris as a surrogate bioindicator species to assess soil conditions and their effects on germination and growth. We used laboratory-based experiments and statistical models to analyze the influence of biotic and abiotic factors, including soil nutrients, vegetation cover, and climatic changes. The study’s findings indicate that soil conditions at the examined sites do not pose significant limitations to germination and plant growth. This suggests that the studied sites retain the potential for recruitment, despite the observed variations in soil and site conditions. The results imply that other factors, such as historical climate changes and herbivory, may be impeding recruitment success. While further research is needed to identify the specific factors hindering recruitment and develop effective conservation strategies, this study provides valuable insights into the potential limitations affecting B. miersii recruitment. These findings highlight the importance of considering multiple environmental factors beyond soil conditions when addressing recruitment challenges in threatened species.